(3MceI GdYjfs - (3Ydj Hf YeQ Hf Ydj GdcGJHj GdbRhjfj, fLe GdOjf, hjbGd dg OHjQGf,J (B675 (3g` s ((3fYeGf GdNhGQRei s)
(3ChdgG (B:s
(3dfG ajg NjQ aGYdehG GNhGJi Cf LeGYI ef QabGFi habge Gddg hGjGce s
(3BNQgG (B:s
(3gjFGJ GfaYGdjI cGdVMc hGdHcGA hGdNLd hGdMjG hgj bhI hdjcf gPG BNQ eG CQOfG GjQGOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B159s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B685s
Keywords: (3GdadSaI hGdefWbs